Thermal Properties of Food and Biopolymer Using Relaxation Techniques - Mahanta A.K.; Rana D.; Sen A.K.; Maiti P. (My University, 2025)
Thermal properties of foods are of great importance for understanding the relationship between food properties and changes in food quality. Concentrated food products (low-moisture and frozen foods) tend to form an amorphous, non-crystalline structure. Several glass transition-related changes in such foods greatly affect the stability, for example, stickiness and caking of powders, crystallization of amorphous sugars, recrystallization of gelatinised starch, ice formation and recrystallization of frozen foods. Similarly, various types of structural changes and molecular dynamics are observed in the biopolymers with heat treatment. In this chapter, an attempt is made to correlate the relationship between glass transition, water plasticisation and relaxation times in food systems, and for the biopolymers which will help to control the rates of changes in food processing and storage. Lastly, an attempt is made to evaluate the applicability of the biopolymers in different applications. © 2017 JohnWiley & Sons Ltd.